2018
DOI: 10.4102/sajr.v22i2.1353
|View full text |Cite
|
Sign up to set email alerts
|

Understanding indications and defining guidelines for breast magnetic resonance imaging

Abstract: Magnetic resonance imaging (MRI) of the breast is the most sensitive imaging modality for detecting cancer. With improved scan resolution and correctly applied clinical indications, the specificity of breast MRI has markedly improved in recent years. Current literature indicates an overall sensitivity for breast MRI of 98% – 100% and specificity of 88%. By comparison, the sensitivity and specificity for mammography is in the region of 71% and 98%, respectively. In particular, the very high negative predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
0
15
0
3
Order By: Relevance
“…Studies show that breast MRI has a promising role in breast cancer management and can be used in addition to mammography in diagnosing this type of neoplasia, especially in patients with dense breasts [ 40 , 41 ]. It is demonstrated that MRI has a higher sensitivity in detecting breast neoplasia than mammography and ultrasound (also in women with prostheses), which makes it an effective technique in investigating cancer recurrence [ 42 , 43 , 44 , 45 , 46 ]. Furthermore, it can detect neoplasia at an early stage, compared to mammography or US, being able to differentiate benign lesions from the benign-appearing ones [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that breast MRI has a promising role in breast cancer management and can be used in addition to mammography in diagnosing this type of neoplasia, especially in patients with dense breasts [ 40 , 41 ]. It is demonstrated that MRI has a higher sensitivity in detecting breast neoplasia than mammography and ultrasound (also in women with prostheses), which makes it an effective technique in investigating cancer recurrence [ 42 , 43 , 44 , 45 , 46 ]. Furthermore, it can detect neoplasia at an early stage, compared to mammography or US, being able to differentiate benign lesions from the benign-appearing ones [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that MRI has a higher sensitivity in detecting breast neoplasia than mammography and ultrasound (also in women with prostheses), which makes it an effective technique in investigating cancer recurrence [ 42 , 43 , 44 , 45 , 46 ]. Furthermore, it can detect neoplasia at an early stage, compared to mammography or US, being able to differentiate benign lesions from the benign-appearing ones [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that BI-RADS has only recently been mandated for mammographic reports in BC, this information was unavailable in more than half of the patients included in this study, limiting the generalizability of these ndings. Nevertheless, a higher density of breast tissue has been generally accepted as an indication for MRI [22], partially due to better fat suppression and a higher resolution [14]. This is particularly relevant prior to NAT where disease extent and accurate staging are utilized for assessment of treatment response and locoregional treatment planning [24].…”
Section: Discussionmentioning
confidence: 99%
“…A two-step procedure typically employed to diagnose TNBC is imaging and immunohistochemistry (IHC) [ 38 ]. Imaging encompasses a mammogram, an ultrasound of the breast along with magnetic resonance imaging (MRI) [ 39 ]. A mammogram requires a minimal dosage of radiation that does not easily penetrate the breast tissues [ 40 ].…”
Section: Current Diagnosismentioning
confidence: 99%